Haematological Profiles of Lactating Nili-Ravi Buffaloes Under Heat Stress-Alleviated Conditions During Sub-tropical Summer Season - Das, K. S.; Singh, J. K.; Nayan, V. (Journal of Buffalo Science, 2014)
The experiment was conducted using forty two Nili-Ravi lactating buffaloes of Central Institute for Research on Buffaloes, Regional Station-Bir Dosanjh, Nabha, Patiala, Punjab to investigate the effect of heat stress-alleviated conditions on haematological profile in Nili-Ravi buffaloes during hot-dry (HD) and hot-humid (HH) season. All buffaloes were uniformly divided into two groups of twenty one in each group considering their lactation number, stage of lactation, body weight, dam’s milk yield and milk yield in current lactation. Out of which ten buffaloes from each group were selected for blood sampling considering those above factors. The control (T0) group were kept in a separate shed without any extra nutrient supplementation and modification in microclimate and management. The treatment (T1) group was supplemented with niacin@6 gm/buffalo/day, yeast@10 gm/buffalo/day and mustard oil @150gms/buffalo/day. They were provided curtains and mist fans in the shed. Feeding time, frequency and type of ration were also altered. During HD period, T0 group exhibited higher (P<0.002, P<0.05) WBC (17.2 x 109 /L), and lymphocyte (12.52 x 109 /L) counts and lymphocyte per cent (69.46 %) than T1 group (12.32 x 10 9 /L, 7.32 x 10 9 /L and 59.68%, respectively). Similar results were recorded during hot humid season in T0 and T1 group. The neutrophil per cent differed significantly between T0 and T1 group under HD (P<0.001) and HH (P<0.006) season. The study indicated that heat stress during sub-tropical summer months affected the haematology of lactating buffaloes and the stress could be reduced through the change (use of fans and curtains, nutritional supplementations, and feeding alterations together in the form of one package) of microclimate.